Nasopharyngeal carriage of Staphylococcus aureus among imprisoned males from Brazil without exposure to healthcare: risk factors and molecular characterization - Witzel, Claudia de Lima [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Martins de Souza, Camila Sena [UNESP]; Moraes Riboli, Danilo Flavio [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Biomed Central Ltd., 2014)
Background: Previous studies report high prevalence of Methicillin-resistant Staphylococcus aureus (MRSA) colonization among imprisoned populations. However, there are no data on that prevalence in Brazilian correctional institutions.Findings: We tested 302 male prisoners for nasopharyngeal colonization with Staphylococcus aureus from February 2009 through April 2010. The overall isolation rate of S. aureus was 16.5% (50/302). Men who had sex with men, users of inhalatory drugs and those with previous lung or skin diseases were more likely to be colonized with S. aureus. MRSA was isolated from 0.7% of subjects (2/302). The two Community-associated (CA)-MRSA belonged to ST5 but were unrelated based on the PFGE results. Both harbored SCCmec IV, and did not possess the Panton-Valentine Leukocidin gene.Conclusion: We found low prevalence of S. aureus and CA-MRSA among prisoners. MRSA isolates ST5 from two subjects harboured SCCmec IV and presented different PFGE patterns.
Keywords: Staphylococcus aureus; MRSA; Inmates